2008
DOI: 10.1097/gme.0b013e31815f8917
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover marker profile in relation to the menstrual cycle of premenopausal healthy women

Abstract: Levels of some bone turnover markers varied during the menstrual cycle. A statistically significant change in sCTX (9.46%) occurred between the FP and LP of the menstrual cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 40 publications
(21 reference statements)
4
24
4
1
Order By: Relevance
“…In contrast, previous reports in premenopausal women showed that FSH was significantly correlated with bone resorption markers 18,25 . In addition, Gass and colleagues found that serum CTX levels during the follicular phase were significant higher than in the luteal phase 28 . The discrepancy of our results with previous reports may be explained by ethic and geographical differences, the smaller number of women in the premenopausal group, or the different resorption parameters measured in previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, previous reports in premenopausal women showed that FSH was significantly correlated with bone resorption markers 18,25 . In addition, Gass and colleagues found that serum CTX levels during the follicular phase were significant higher than in the luteal phase 28 . The discrepancy of our results with previous reports may be explained by ethic and geographical differences, the smaller number of women in the premenopausal group, or the different resorption parameters measured in previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, the greatest reduction in serum CTX-I concentration occurred just after ibandronate dosing and then decreased to a minimum level just before the next dose. A monthly pattern of serum CTX-I fluctuations due to variations in hormone levels related to the menstrual cycle subphases has been observed in healthy premenopausal women [4]. A cyclical pattern is also observed with monthly ibandronate treatment but is related to time from last dose.…”
Section: Discussionmentioning
confidence: 79%
“…Bone turnover can be assessed using biochemical markers of bone turnover (BTMs), which are released as a result of the bone remodeling process and detectable in urine and blood [3]. In a study of BTMs in healthy premenopausal women, levels of the bone resorption marker serum C-terminal cross-linking telopeptide of type 1 collagen (CTX-I) were found to vary with phases of the menstrual cycle [4]. The total monthly fluctuation in serum CTX-I levels was reported to be ∼9.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Since BTM serum levels have been reported to vary depending on menstrual cycle phase (Gass et al 2008), we recruited oral contraceptive users to minimize the influence of menstrual phase variations in endogenous sex hormones on BTM levels. The exclusion criteria were: 1.…”
Section: Methodsmentioning
confidence: 99%